(untitled) (Journal of Contemporary Philology, 2020)
The study establishes a theory for analysis of popular music according to Theodor Adorno’s philosophy, through the concepts of standardization, pseudo-individualization, and the two types of listening to popular music: rhythmic-obedient and emotional. It points out his philosophy and continues with a critical analysis of contemporary products of popular music – American artist Daniel Lopatin’s Eccojams, Part 1. It also refers to some contemporary music critics such as Simon Reynolds and Marvin Lin. This work is an attempt to look at the attitude towards popular music during the first half of the 20th century and the condition of its influences today, at the beginning of the 21st century. The study uses some aspects of Adorno’s negative attitude towards the value of modern cultural products and it addresses the attempts of contemporary artists and theorists to discover ways out of the illusion and repressive function of the modern cultural industry. At the end, all this is connected with the use of repetitiveness and the modern effects of music technology of Lopatin as a way of setting new narratives in popular culture.